A pulsed uniform Laval expansion coupled with single photon ionization and mass spectrometric detection for the study of large molecular aggregates. Issue 39 (21st October 2015) - Schläppi, Bernhard; Litman, Jessica H.; Ferreiro, Jorge J.; Stapfer, David; Signorell, Ruth
<x xml:space="preserve">Abstract</x> The combination of Laval expansions with single photon VUV ionization and linear time of flight mass spectrometry allows one to study weakly-bound molecular aggregates under equilibrium conditions.